Efektivitas Manajemen Pemasaran dalam Meningkatkan Jumlah Konsumen Rumah Makan Ayam Goreng Nelongso di Bangkalan - Fadilatul Akmalia; Octaviana Arisinta; Romiftahul Ulum (J-MAS (Jurnal Manajemen dan Sains), 2023)
This study discusses the effectiveness of marketing management in increasing consumers of Nelongso Fried Chicken restaurants in Bangkalan. The purpose of this research is to find out how the effectiveness of marketing management is in improving the nelongso Fried Chicken restaurant in Bangkalan. This type of research is descriptive qualitative research. Data collection methods carried out in this study were observation, interviews, and documentation. Furthermore, technical analysis of data in three steps, namely data reduction, data presentation, and drawing conclusions. After the authors conducted data analysis, a result was found from the effectiveness of marketing management in increasing consumers of Nelongso Fried Chicken restaurants in Bangkalan implementing 4P, namely: (1) product, by providing a menu of food and drinks with various menus with different tastes, (2) price , by setting prices that consumers can reach, (3) place, providing a comfortable place and having complete facilities, (4) promotion, using various social media and consumers, namely word of mouth.